RUANG TERBUKA HIJAU DALAM PEMBANGUNAN BERKELANJUTAN DI DAERAH KHUSUS IBUKOTA JAKARTA (Lex Jurnalica, 2017)
AbstractGreen open spaces are elongated / lane and / or clumped areas, with more open use, where plants grow, whether naturally grown or intentionally planted. The purpose of this research is first, to know law enforcement against green open space fulfillment in DKI Jakarta. Secondly, to find out the obstacles found by the Jakarta Parks and Cemetery Agency in the procurement of land for the fulfillment of green open space park in DKI Jakarta. The method in this research is qualitative with secondary data collection and literature study and primary data is taken with the instrument of interview with the official or authorized staff in related institution. The results showed that green open space of DKI Jakarta has not been fulfilled by 30% of the total area of Jakarta Capital City. The green open spaces of the park under the Jakarta Parks and Cemetery Department resulted from the refueling of SPBU, namely: Central Jakarta area there are 10 locations with an area of 13,022.00 M. North Jakarta area there are 3 locations with an area of 4,275.00 M2. West Jakarta area there are 3 locations with an area of 3.18800 M2. South Jakarta area there are 7 locations with an area of 12,277.00 M2. East Jakarta area there are 3 locations with an area of 4,123.00 M2. The Thousand Islands Region is no refunction. Obstacles encountered related to the procurement of land for green open spaces of the park, namely: first, the existence of disagreement in the community related to the procurement of land destined for the park. Second, the land in dispute. Third, in spatial planning every zoning / allotment is coordinated to different SKPD. Keywords: Green open space, sustainable development, DKI JakartaÂ AbstrakRuang terbuka hijau adalah area memanjang/jalur dan/atau mengelompok, yang penggunaannya lebih bersifat terbuka, tempat tumbuh tanaman, baik yang tumbuh secara alamiah maupun yang sengaja ditanam. Tujuan penelitian ini adalah pertama, untuk mengetahui penegakan hukum terhadap ketentuan pemenuhan ruang terbuka hijau di DKI Jakarta. Kedua, untuk mengetahui hambatan-hambatan yang ditemukan oleh Dinas Pertamanan dan Pemakaman DKI Jakarta dalam pengadaan tanah untuk pemenuhan ruang terbuka hijau taman di DKI Jakarta. Metode dalam penelitian ini adalah kualitatif dengan pengumpulan data sekunder dan studi kepustakaan serta data primer diambil dengan instrumen wawancara dengan pejabat atau staf yang berwenang pada instansi terkait. Hasil penelitian menunjukkan bahwa ruang terbuka hijau DKI Jakarta belum terpenuhi sebesar 30% dari luas wilayah DKI Jakarta. Ruang terbuka hijau taman yang pengelolaannya di bawah Dinas Pertamanan dan Pemakaman DKI Jakarta hasil refungsi SPBU yaitu: Wilayah Jakarta Pusat terdapat 10 lokasi dengan luas 13.022,00 M. Wilayah Jakarta Utara terdapat 3 lokasi dengan luas 4.275,00 M2. Wilayah Jakarta Barat terdapat 3 lokasi dengan luas 3.18800 M2. Wilayah Jakarta Selatan terdapat 7 lokasi dengan luas 12.277,00 M2. Wilayah Jakarta Timur terdapat 3 lokasi dengan luas 4.123,00 M2. Wilayah Kabupaten Kepulauan Seribu tidak ada refungsi. Hambatan yang ditemui berkaitan dengan pengadaan tanah untuk ruang terbuka hijau taman, yaitu: pertama, adanya ketidakesepakatan di kalangan masyarakat berkaitan dengan pengadaan tanah yang diperuntukkan bagi taman. Kedua, tanah dalam sengketa. Ketiga, dalam perencanaan tata ruang setiap zonasi/peruntukan dikoordinasikan kepada SKPD yang berbeda-beda.Â Kata kunci: Ruang terbuka hijau, pembangunan berkelanjutan, DKI Jakarta.